Long-term sustainability of African school feeding programs, a review - Mainje, Michael; Matumba, Limbikani; Harvey, Jagger J. W.; Phiri, Horace; Gama, Aggrey P.; Phiri, Alexander; Phangaphanga, Innocent; Chizimba, Robert; Wamey, Beatrice; Gallagher, Patrick; Rutto, Emily; Leslie, John F. (Frontiers in Sustainable Food Systems, 2024)
Sustainable school feeding programs (SFPs) in sub-Saharan Africa play a vital role in addressing malnutrition and poor educational outcomes among children. It is critical to contextualize SFPs to local needs and resources, while retaining the twin universal goals of alleviating hunger and promoting education, and the associated strengthening of health, nutrition and social protection. The effective implementation and continuity of such programs, however, present challenges. Key hurdles to establishing and maintaining effective SFPs in sub-Saharan Africa were assessed, as well as strategies to address these challenges. We searched three databases for articles published between 2012 and 2023 with combinations of the keywords: “school feeding,” “school meals,” “sustainability,” “sustainable,” and “long-term.” Of >25,000 identified articles, 21 focused on quantitative and qualitative evaluations of sustainability in primary school SFPs with children aged 6–14. Themes discussed in these articles fall into four broad areas: policy, operations, community involvement and ancillary activities. Successful SFPs in sub-Saharan Africa differ substantively from those in higher income countries. Home grown SFPs are a common route to follow to transition from external donor support, and increase community involvement. The SMP+ meal planner from the World Food Program is widely used to develop nutritious, acceptable meals based on locally available foodstuffs. School gardens and means to access sufficient fuel, usually firewood, for cooking are important concerns in sub-Saharan Africa, but are not usually a concern in higher income countries. By utilizing locally sourced foods and involving students in school gardens and meal planning activities, more comprehensive nutrition education can occur and students can better understand ways to utilize the food available to their household. In conclusion, we provide target areas for policymakers and practitioners to address when designing SFPs that can be sustained for the long term in sub-Saharan Africa and other low and middle-income countries.